CONDITIONS OF IMPROVING THE QUALITY OF ACTIVITY METHODOLOGICAL SERVICE OF THE MEDIUM AND HIGH SCHOOL (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to the issue of improving the professional skills of the pedagogical staff, where a person and it's (his or her) own potential is of particular importance. The conditions of improvement are presented in the article.